Benefits of Cardiac Rehabilitation in Heart Failure Patients According to Etiology: INCARD French Study. Issue 7 (February 2015) - Koukoui, François; Desmoulin, Franck; Lairy, Gérard; Bleinc, Dominique; Boursiquot, Ludovic; Galinier, Michel; Smih, Fatima; Rouet, Philippe
Abstract : Abstract: We investigated the impact of heart failure (HF) etiology on the outcome of cardiac rehabilitation (CR) assessed by functional and clinical parameters. Treatment of chronic HF requires multidisciplinary approaches with a recognized role for CR. INCARD is a French study aimed at evaluating the benefits of sustainable CR in coronary (C) and noncoronary patients (NC) treated and educated during a 24-month period of follow-up. Prospective, monocentric patients with HF underwent inpatient physical training followed by a home-based program. Evaluations were performed at inclusion, discharge, 3 months after discharge, and subsequently every 6 months over the 24 months of outpatient rehabilitation. A total of 147 HF patients with left ventricular ejection fraction (LVEF) <40 were admitted to the CR center, 63 accepted to join INCARD (29 C and 34 NC). Although the C participants C having both an echocardiographic LVEF and an initially lower peak VO2, inpatient rehabilitation improved all functional parameters. Only NC showed an improved LVEF during the first 3 months of outpatient-follow-up. The main outcome of the outpatient rehabilitation was a trend toward stabilization of clinical and laboratory parameters with no significant difference between C and NC. This study confirms the benefits of initial HF inpatient rehabilitation and encourages prolonged outpatient monitoring. The results on functional parameters suggest exercise training should be conducted regardless of the HF etiology. Abstract : Supplemental Digital Content is available in the text